2020
DOI: 10.5397/cise.2020.00283
|View full text |Cite
|
Sign up to set email alerts
|

Can manipulation under anesthesia alone provide clinical outcomes similar to arthroscopic circumferential capsular release in primary frozen shoulder (FS)?: the necessity of arthroscopic capsular release in primary FS

Abstract: Background: We evaluated the need for arthroscopic capsular release (ACR) in refractory primary frozen shoulder (FS) by comparing clinical outcomes of patients treated with ACR and manipulation under anesthesia (MUA). Methods: We assessed patients with refractory primary FS, 54 patients (group A) who were treated with MUA and 22 patients (group B) who were treated with ACR. In group A, manipulation including a backside arm-curl maneuver was performed under interscalene brachial block. In group B, manipulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, the literature disagrees with this statement, as most studies have confirmed similar treatment outcomes with both options. 36,53…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature disagrees with this statement, as most studies have confirmed similar treatment outcomes with both options. 36,53…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature disagrees with this statement, as most studies have confirmed similar treatment outcomes with both options. 36,53 Although the 2 groups strongly agreed that either surgical intervention should be done between 4 and 9 months, the groups remained almost equally divided on whether intervention should occur early (4-6 months) or late (7-9 months). Although most of the literature supports surgical treatment between 6 and 9 months, 52,54 a recent study concluded that the results of surgery before 6 months (mean, 3.8 months) or after 6 months (mean, 11.1 months) are similar.…”
Section: Trends and Consensus Regarding Surgical Practices And Progno...mentioning
confidence: 99%
“…The authors prefer to inject 40 mg of triamcinolone and 10 ml of 0.25% Bupivacaine to minimise postoperative pain and inflammation. Many other authors too prefer post MUA injection of steroid and local anaesthetic agent [83,84]. However, concrete evidence for the benefit of the same is lacking.…”
Section: Operative Management Of Frozen Shouldermentioning
confidence: 99%
“…Post MUA or ACR, authors prefer to inject 40 mg of Triamcinolone along with 10 ml of 0.25% Bupivacaine to minimise post-procedure inflammation and pain. Although many authors prefer injecting steroid post-ACR [83,[104][105][106], only a few report superior outcome after the injection [106]. However, larger consensus regarding utility of steroid injection post-ACR is lacking.…”
Section: Operative Management Of Frozen Shouldermentioning
confidence: 99%
See 1 more Smart Citation